In Silico Study, Synthesis, Characterisation And Cytotoxicity Activity Of New Chalcone, Pyrazoline And Pyrimidine Derivatives - Alanazi, Menier Meteb Mohammad (2021)
Three new series of novel chalcone derivatives with promising anti-cancer activity were studied which are two series of tri-chalcone derivatives S1(1-7) and S2(1-7) and a series of mono-chalcone derivatives S3(1-7). Another three series of pyrazoline Ai-Aiii and pyrimidine Bi-Biii from mono-chalcone were also studied by AutoDock 4.2.6. The intermolecular interactions and binding energies of the proposed compounds were determined to be synthesised and characterized. The best compounds were selected for further investigation by MD simulation using AMBER 14. The following compounds of chalcone derivatives S1-1, S1-2, S2-1, S2-2, S3-1, S3-(3-5), pyrazoline derivatives Ai-Aiii and pyrimidine Bi-Biii from mono-chalcone S3-(1,3-5) demonstrated the highest binding affinity for the interaction with the active EGFR binding site. These selected chalcones, pyrazoline and pyrimidine derivatives were synthesised to test their cytotoxicity activity against breast cancer cell lines and EGFR inhibitory activity. Synthesis of the chalcone derivatives was performed via a Claisen-Schmidt condensation while the ring-closing of mono-chalcones formed the pyrazoline and pyrimidine derivatives. The chemical structures of the synthesised compounds were confirmed using spectroscopic techniques such as FTIR, 1H NMR, 13C NMR and elemental analysis (CHN analysis). Antiproliferative activity of the synthesised compounds against breast cancer cell lines (MCF-7 and MDA-MB-231) were evaluated using 3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyltetrazolium bromide assay (MTT).